A practical method for the analysis of genetic algorithms - Alshaikhli, Imad Fakhri Taha (Science Publishing Corporation, 2011)
In this research, a practical method was proposed for the analysis of genetic algorithms for the sake of proving their efficiency, showing the weak points, and checking the performance by answering most of the important questions related. The experimental result done on some of the known genetic algorithms show the usefulness of the proposed method in improving the quality of genetic algorithms.